USING A MACROECONOMIC APPROACH IN ASSESSING BUSINESS ACTIVITY - GONCHAR, Olga; MOROZ, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study develops an integrated macroeconomic framework for assessing business activity in Ukraine, grounded in the synthesis of sectoral indicators, firm-level performance metrics, and macroeconomic aggregates. The methodological foundations of applying a macroeconomic approach to assessing business activity are considered, emphasizing the interdependence between microeconomic operating results and dynamics at the macro level. Particular attention is paid to the system of indicators that reflect production scale, profitability, financial sustainability, and investment behaviour of enterprises. The research justifies the role of macroeconomic cycles, structural shocks, and price dynamics in shaping firms’ performance trajectories and underscores the necessity of multi-component evaluation tools that can capture both short-term fluctuations and long-term structural patterns. The study examines the dynamics of output sales, operational profitability, financial results before taxation, capital investment flows, and the sectoral distribution of loss-making enterprises. These indicators are interpreted in relation to key macroeconomic aggregates such as GDP, consumer demand, trade balances, and production indices. The analytical part highlights the sensitivity of business activity to external shocks, including the pandemic-related disruptions in 2020 and the deep systemic contraction in 2022. At the same time, empirical evidence reveals the capacity of enterprises to restore operational efficiency during periods of partial macroeconomic stabilization. An integral index of business activity was constructed using normalized values ​​of real sales, operating profitability, financial results, and capital investment dynamics. Component weights are determined through a principal component–based weighting scheme. The resulting index, scaled from 0 to 100, captures major shifts in business behaviour: moderate growth in 2018-2019, contraction during the pandemic, peak expansion in 2021, a collapse due to wartime disruptions in 2022, and a subsequent recovery in 2023-2024. The index serves as a consolidated diagnostic tool enabling cross-year comparison, identification of cyclical turning points, and evaluation of the resilience of the business sector under macroeconomic stress conditions.